John Miles Foley's World of Oralities Text, Tradition, and Contemporary Oral Theory - Amodio, Mark C. (Borderlines, 2020)
This collection brings together newly commissioned and cutting-edge essays on oral text and tradition ranging from the ancient and medieval world to the present day by a leading group of European and North American oral theorists. Using a range of materials including the Bible, Greek epic, Beowulf, Old Norse and Old English riddles, and medieval music, the contributors collectively work to refine, challenge, and further advance contemporary Oral Theory, an interdisciplinary school of thought heavily influenced by John Miles Foley, whose work provides the jumping-off point for this volume. The book includes a useful introduction to the history of oral theory and Foley's ground-breaking and influential work.